2020
DOI: 10.1002/med.21754
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of melanocyte death in vitiligo

Abstract: Vitiligo is an autoimmune depigment disease results from extensive melanocytes destruction. The destruction of melanocyte is thought to be of multifactorial causation. Genome‐wide associated studies have identified single‐nucleotide polymorphisms in a panel of susceptible loci as risk factors in melanocyte death. But vitiligo onset can't be solely attributed to a susceptive genetic background. Oxidative stress triggered by elevated levels of reactive oxygen species accounts for melanocytic molecular and organe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(131 citation statements)
references
References 249 publications
(318 reference statements)
1
124
1
5
Order By: Relevance
“…On the other hand, TXN was highly expressed in vitiligo skin samples ( Figure 5 ) and controlled the cellular redox environment ( Lu and Holmgren, 2014 ). And previous studies had demonstrated that oxidative stress was critical for the progression of vitiligo ( Chang et al, 2017 ; Ma et al, 2018 ; Yi et al, 2019 ; Chen et al, 2021 ). However, there was no study to report the relationship between TXN and vitiligo, which attracted our attention.…”
Section: Resultsmentioning
confidence: 98%
“…On the other hand, TXN was highly expressed in vitiligo skin samples ( Figure 5 ) and controlled the cellular redox environment ( Lu and Holmgren, 2014 ). And previous studies had demonstrated that oxidative stress was critical for the progression of vitiligo ( Chang et al, 2017 ; Ma et al, 2018 ; Yi et al, 2019 ; Chen et al, 2021 ). However, there was no study to report the relationship between TXN and vitiligo, which attracted our attention.…”
Section: Resultsmentioning
confidence: 98%
“…TLR4 is expressed on melanocytes and believed to react to endogenous heat-shock proteins and initiate autoimmunity [ 20 ] by stimulating dendritic cells (DCs) to present melanocyte-specific antigens to T cells in lymphoid tissues [ 21 ]. Activated DCs release a cascade of cytokines that stimulate keratinocytes and activated NK cells together with chemo-attracted melanocyte-specific CD8 + T cells leading to the T cell-mediated autoimmune destruction of melanocytes [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in the glutathione system, one of the major endogenous antioxidant defenses, were reported for alopecia areata [ 58 ], psoriasis [ 65 ], oral lichen planus [ 70 ] and atopic dermatitis [ 73 ]. In addition, vitiligo is also accompanied by decreased antioxidant defenses [ 67 ] and elevated oxidation products [ 68 , 69 ] that mediate the death of melanocytes [ 74 ]. Deregulated redox homeostasis and oxidation of macromolecules further accompany cutaneous disease pathology [ 40 , 61 , 68 , 71 ].…”
Section: Natural Products With Antioxidant Activity As Adjuvant Therapeutic Approach In Dermatologymentioning
confidence: 99%